2014
DOI: 10.1097/01.mib.0000442728.74340.fd
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia in Inflammatory Bowel Diseases in European Countries

Abstract: The overall prevalence of anemia in patients with Crohn's disease was 27% (95% confidence interval, 19-35) and 21% (95% confidence interval, 15-27) in patients with ulcerative colitis. Thereby, 57% of the anemic patients were iron deficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
74
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 26 publications
11
74
0
4
Order By: Relevance
“…We confirmed that despite significant beneficial effects on disease activity and clinical outcomes, anti-TNF therapy had only a modest effect on patients’ Hb levels. We found that the prevalence of anemia in IBD patients who start anti-TNF treatment was 38.1% which is similar to other reports on the prevalence of anemia in IBD (2123). It is especially important to note that one year after the initiation of anti-TNF therapy, the prevalence of anemia remained unchanged at 36.6% despite the initiation of potent anti-inflammatory treatment and the iron supplementation.…”
Section: Discussionsupporting
confidence: 90%
“…We confirmed that despite significant beneficial effects on disease activity and clinical outcomes, anti-TNF therapy had only a modest effect on patients’ Hb levels. We found that the prevalence of anemia in IBD patients who start anti-TNF treatment was 38.1% which is similar to other reports on the prevalence of anemia in IBD (2123). It is especially important to note that one year after the initiation of anti-TNF therapy, the prevalence of anemia remained unchanged at 36.6% despite the initiation of potent anti-inflammatory treatment and the iron supplementation.…”
Section: Discussionsupporting
confidence: 90%
“…This prevalence is slightly higher than that published recently in a meta-analysis by Filmann et al: 24% of 2,192 European patients with IBD had anemia [7]. Other studies show that up to 68% of inpatients with IBD had anemia [8,9].…”
Section: Discussionmentioning
confidence: 68%
“…Over half of the IBD patients were found to have anemia at least once during their follow-up. Recent studies conducted mostly in Europe, report that the point prevalence of anemia in IBD is between 20 and 40% (10,11). However, there is no data regarding the period prevalence in large cohorts of IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anemia appears to be lower in outpatients when compared to hospitalized IBD patients (10). A recent meta-analysis of European studies with 2192 patients, mainly treated in tertiary referral centers, showed an overall prevalence of anemia of 27% [95% confidence interval (CI), 19–35] for Crohn’s disease (CD) and 21% (95% CI, 15–27) for ulcerative colitis (UC) (11). Most existing data describes point prevalence, whereas the period prevalence of anemia in IBD patients is largely unknown.…”
Section: Introductionmentioning
confidence: 99%